The Role Of AROMAZA-Based Educational Information Systems In Increasing Parental Involvement - Nadiah Afkarina Rohman; Nanang Qosim; M. Fuad Badruddin (Managere: Indonesian Journal of Educational Management, 2025)
This study explores the role of the MA ZAHA Robot Assistant (AROMAZA) in increasing parental involvement in the educational process. The research investigates how digital tools can improve communication between schools and parents, fostering a stronger partnership supporting student academic development. The significance of this study lies in addressing the gap in the literature regarding integrating educational technology in Islamic schools, particularly focusing on how tools like AROMAZA can enhance parent-school relationships. Using a qualitative case study approach, data were collected through interviews with parents, teachers, and administrative staff, as well as direct observation and review of school policies and academic records. The study finds that AROMAZA significantly improves the speed of information delivery, enhances parent participation in school activities, and provides real-time access to students' academic progress. Despite challenges related to technology adoption, the findings suggest that AROMAZA plays a crucial role in promoting transparency, supporting parental engagement, and reducing administrative burdens. The implications of this research highlight the potential of digital platforms in strengthening school-parent partnerships, offering valuable insights for educational institutions seeking to implement similar technologies to enhance parental involvement and improve academic outcomes.